SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE TO IMPROVE SLEEP QUALITY FOR POSTPARTUM MOTHERS - Nana Andriana; Tri Nur Kristina; Dwi Susilawati (Nurse and Health: Jurnal Keperawatan, 2023)
Background: Sleep quality disorders are a problem that postpartum mothers often experience. The postpartum is the period after giving birth or commonly called the puerperium, which is the period after giving birth that is needed to restore the uterine organs. Post-partum mothers experience sleep quality disorders both due to new roles and changes during the postpartum period. Sleep quality that is not treated properly can bring changes that can affect physical and psychological problems. Thus, it needs to interfere with the sleep quality of post-partum mothers. Objectives: This study aimed to prove that the Spiritual Emotional Freedom Technique (SEFT) was also beneficial in improving sleep quality in postpartum mothers. Methods: This study used a quasi-experimental pre-and post-test design with a control group. The research subjects were 56 postpartum mothers treated at Sultan Agung Islamic Hospital Semarang in June and September 2021, divided into intervention and control groups. The intervention was carried out twice a week for four weeks, with a SEFT duration of 20 minutes. The control group received standard therapy in the form of dhikr therapy. The Pittsburgh sleep quality index (PQSI) questionnaire used seven assessment components to measure research outcomes. The univariate analysis used central tendency in the form of the mean, median, and standard deviation. The different test of sleep quality before and after the intervention in the intervention group was carried out by the Wilcoxon match pair test (abnormal distribution), while the control group used paired t-test (normal distribution). For the mean difference test between groups, it used Mann Whitney test. Results: The mean score of sleep quality in the intervention group before treatment was 10,86 + 1,79 (poor sleep quality) and after treatment decreased significantly (p=0,00) to 5,25 + 1,46 (still in poor sleep quality). The quality of sleep in the control group before treatment was 10,89 + 1,89 and after the intervention was 10,71 + 2,35 with p=0,47. The components of subjective sleep quality, sleep latency, sleep duration, and sleep disturbance in the intervention group were significantly lower than in the control group. Conclusion: The SEFT intervention can significantly improve sleep quality in postpartum mothers, but it is still in the poor category. Besides, the sleep quality score can be considerably improved, especially in four of the seven components.